Fabrication and sensing properties of a micro-humidity sensor system using CMOS technology - Lee, Sung Pil (Electronic materials letters, 2010)
A micro-humidity sensor system is designed and fabricated by 0.8 μm analog mixed CMOS technology. The integrated sensor system consists of an n-channel differential FET humidity sensor, a Wheatstone bridge humidity senor, and an operational amplifier block, respectively. The differential sensor employs carbon nitride films as a new sensing material and has a pair of transistors, a sensing transistor and a non-sensing transistor (reference transistor), to eliminate unexpected effects. The drain current of the FET humidity sensor increases from 0.88 mA to 0.99 mA as the relative humidity increases from 10 %RH to 70 %RH.